IoT for agriculture optimization: preliminary results of a tropical precision farming project - Gibeaux, Soizic (2022)
The agricultural activities need optimal soil and the agro-climatic conditions in the production areas such as Cerro Punta in Panama. Among the innovative technological alternatives, there are tools that can provide farmers with information describing the agro-meteorological conditions of some areas, such as precision agriculture. Due to the data range of wireless communication and low power capabilities, one of the most promising technologies for precision farming is WSN with integrated LoRa systems and energy self-sufficient. This study presents the methodology of the first LoRa WSN project destined to precision agriculture in Panama, and bring the preliminary results in the evaluation of LoRa signal, micro solar panel efficiency and environmental data. In the tropical vegetation of this part of the country, the range of LoRa communication is smaller than theoretically expected. The efficiency of the solar panels is enough to maintain the batteries always charged. Finally, slightly different microclimates have been highlighted between two close monitored areas.